Navigating the unknown: College transitions of third culture individuals - Justin Weller, (Journal of International Students, 2024)
Research on third-culture individuals (TCIs) is an emerging topic in college student development. However, while emerging literature on TCIs exists, research on TCIs’ personal development in postsecondary contexts is still lacking. This literature review addresses this issue. In this review, I argue that the literature predominantly illustrates that TCIs experience a negative transition to college that negatively impacts their personal development. I then synthesize the literature, identifying the background of the research surrounding TCIs. Next, I summarize the four main themes that the literature identifies as struggles that TCIs experience while transitioning into college: family, social connections, mental well-being, and identity construction. I then highlight the important contribution that resilience has to TCIs’ lives in college. I conclude by arguing that recommendations from the literature and practice should be adopted by all postsecondary institutions to better support TCIs.